SUSTAINABLE EXTRACTION AND COMPARATIVE ANALYSIS OF OIL FROM MORINGA AND SOYBEAN SEEDS USING PETROLEUM ETHER: AN ECONOMIC COST ANALYSIS - Theodore U. Nwaneri; Nnadikwe Johnson (SEAN Institute, 2025)
The increase demand and application for oils have engendered more searches for vegetable and seed oil that are of high quality. In this work, extraction and phytochemical analysis and physiochemical characterization of moringa seed and soya bean seed oil was carried out. The seed oil of the plants were extracted using solvent (petroleum ether), standard method was adopted to extract the oil. The parameters of both were determined by physiochemical analysis and calculation. 382g of grounded moringa seed and soya bean seed powder were weighed, and mixed with 1000ml of the petroleum ether in a round bottom flask of soxhlet extraction unit. The extraction process was carried out for three hours (180mins) for the seed powders respectively. The pH of moringa seed oil and soya bean seed oil were recorded as 5.8pH and 5.9pH respectively. The moringa seed yielded 185ml oil which represent 48.4% yield while soya bean seed yielded 61ml of oil which represent 16% yield. The density of both oils in the study research; 0.8363g/ml for moringa seed oil and 0.904g/ml, represent low and medium density food grade oil respectively. Density of oil > 0.92g/ml are regards as high density oil (Abbas A, et al, 2020).The phytochemical analysis showed that both seed oils are healthy plants based oils for human, domestic and industrial application.